Investigation and analysis of structural and electrochemical properties of highly ionic conductive La2-xSrxSn2O7-delta electrolyte for SOFC applications - Melit, Fatima; Bounar, Nedjemeddine; Shaikh, Shabana P. S.; Deshpande, Manish; Steil, Marlu Cesar (Chemical Papers, 2023)
This study primarily focused on the investigation, synthesis and analysis of lanthanum and tin pyrochlores electrolytes for solid oxide fuel cell (SOFC) applications. Ceramic samples with diverse compositions of La2-xSrxSn2O7-delta (x = 0.05, 0.1, 0.15, 0.2, 0.25, and 0.3) were synthesized by using solid-state reaction (SSR) methods. The prepared La2-xSrxSn2O7-delta samples were characterized by using X-ray diffraction, scanning electron microscopy and electrochemical impedance spectroscopy measurements. The results were further interpreted regarding the formation of high oxygen vacancy and structural disorder in the La2-xSrxSn2O7-delta matrix. The doping of lanthanum (La3+) by strontium (Sr2+) had a beneficial and remarkable effect on the structural and electrical properties: the increase in dopant (Sr) concentration decreased the lattice parameters of the crystalline phase and enhanced the creation of oxygen vacancies, which consequently increased the ionic conductivity and decreased the activation energy. Thus, it could be understood that the studied new La2-xSrxSn2O7-delta electrolyte would be one of the potential candidates for intermediate temperature SOFC applications.
Keywords: Electrolyte; Impedance spectroscopy; Ionic conductivity; Pyrochlore; SOFC